Biopsychosocial Path Model of Self-Management and Quality of Life in Patients with type 2 Diabetes - Bazzazian Saeideh (Journal of Bioinformatics And Diabetes, 2017)
Objectives: The present study investigated biopsychosocial predictors (HbA1c, self-efficacy, and social support) of self-management and health-related quality of life among patients with type 2 diabetes. Methods: 160 adults referred to the Iranian Diabetes Society participated in this study. Participants completed General Self-Efficacy Scale, Perceived Social Support, Diabetic Self-care Behaviors scale, and D-39 (diabetics’ quality of life). Results: Data were analyzed with SPSS-19 and Lisrel 8.8, utilizing statistical path analysis. Results revealed significant positive correlations between self-efficacy and social support subscales, self-care and health-related quality of life. Also, HbA1c had not correlation with HRQOL. The final path model fitted well and showed that direct self-care paths with (β = 0.24) and indirect social support with (β = 0.32) had the most effects on health-related quality of life. Conclusions: The results confirmed the theoretical model and scientific evidence for providing psychological solution to promote quality of life in patients with type 2 Diabetes.
Keywords: HbA1c